Sistem Inoklamasi Awards sebagai Media Penilaian Inovasi Daerah pada Innovative Government Awards (IGA) Kabupaten Bangka - Oktaviani, Ajeng; Fujiyanti, Linda; Wathan, M. Hizbul (Jurnal Teknologi, 2025)
Regional innovation plays an important role in improving government performance efficiency and the quality of public services. As a form of appreciation, the Ministry of Home Affairs organizes the Innovative Government Awards (IGA) for regional governments that have successfully implemented innovations in governance, development, and public services. However, the process of collecting and managing innovation data is still carried out manually, making it prone to delays, data loss, and assessment inaccuracies. This study aims to design and develop the Innovation and Proclamation (Inoklamasi) Awards System, a web-based information system that supports the digitalization of innovation data collection, verification, and evaluation processes. The system was developed using an iterative prototyping method, consisting of requirement analysis, design, implementation, and evaluation stages. Its main features include innovation submission by local government agencies (OPD), both automatic and manual data validation, and online assessment by evaluators. Based on the User Acceptance Test (UAT) results, the system achieved a satisfaction rate of 84.75% from 240 respondents, indicating that it is feasible for implementation. The application of the Inoklamasi Awards System is expected to improve administrative efficiency, accelerate workflow, and strengthen coordination among OPD, evaluators, and Bappeda, thereby supporting a transparent and sustainable digital government transformation.